Preparation and antibacterial application of metal nanoparticle modified strontium titanium oxide colloid coating material
By modifying metal nanoparticles on the strontium titanium oxide colloid coating, using photocatalytic and electron transfer processes, the existing antibacterial coatings have been solved in terms of cost, durability, safety and environmental friendliness, achieving efficient, durable and safe antibacterial effects.
Patent Information
- Application Number
- CN202510081177.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
Existing antibacterial coatings have shortcomings in cost, durability, safety and environmental friendliness, and the slow carrier transfer of semiconductor antibacterial materials affects their antibacterial properties.
The strontium titanium oxide colloid coating material is modified by metal nanoparticles, and antibacterial functions are achieved by loading the metal nanoparticles on the strontium titanium oxide semiconductor using photocatalysis and electron transfer processes. The material is prepared by a simple sol-gel method, and the metal particles are modified on the coating surface by spray-photodeposition.
It has achieved improvement in antibacterial performance, reduced the cost of using metal materials, enhanced the broad spectrum of antibacterial properties, and was simple in preparation steps, mild conditions, and had excellent photocatalytic properties and adhesion.
Smart Images

Figure CN119875405A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antibacterial coatings, and in particular relates to the preparation and antibacterial application of a metal nanoparticle-modified strontium titanate colloidal coating material. Background Art
[0002] As people's attention to health and safety continues to increase, the demand for antibacterial coatings is also gradually increasing, especially in public places, hospitals, schools and home environments, the application of antibacterial coatings has become more and more popular. At present, common antibacterial coatings on the market include silver ion antibacterial coatings, copper-based antibacterial coatings and organic antibacterial coatings. Silver ion antibacterial coatings have a broad-spectrum antibacterial effect and achieve efficient and lasting antibacterial effects by destroying bacterial cell membranes and metabolic processes, but the cost is high and long-term use may lead to drug resistance. Copper-based antibacterial coatings use copper ions to bind to bacterial cell membranes to cause cell membrane rupture, have good antibacterial properties and low costs, but are easily oxidized in high humidity environments, affecting appearance and performance. There are many types of organic antibacterial coatings, such as quaternary ammonium salts and phenolic compounds, which have strong antibacterial ability and a wide range of applications, but the antibacterial effect decays over time. In addition, silver ions, copper ions, and organic antibacterial agents pose a potential threat to human health and the environment in the case of long-term contact. Therefore, the development of an efficient, durable and safe antibacterial material remains a key challenge in the current research field.
[0003] While pursuing antibacterial effects, it is necessary to ensure that the materials are harmless to the human body and friendly to the environment, avoid the use of toxic antibacterial agents, and develop green and environmentally friendly antibacterial coatings as the future direction. Semiconductor antibacterial materials are a type of material that uses semiconductor properties, especially photocatalysis and electron transfer processes to achieve antibacterial functions. With the increasing severity of public health issues, especially the increase in antibiotic-resistant bacteria, traditional antibacterial methods face many challenges. Semiconductor antibacterial materials have become a hot spot for research and application due to their unique mechanisms and controllability. However, the antibacterial performance of a single semiconductor is still affected by its slow carrier transport. CN202211476302.7 proposes an antibacterial coating of copper-based titanium dioxide hollow spheres, which is obtained by preparing and coating a precursor and performing surface heat treatment. However, the precursor preparation process of this coating is relatively cumbersome and requires multi-step high-temperature treatment.
[0004] Therefore, providing an antibacterial coating material with excellent antibacterial properties and close integration with the base material is of great significance for the antibacterial and antiseptic properties of household products such as wooden floors, wooden doors, and wooden cabinets. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a preparation and antibacterial application of a metal nanoparticle-modified strontium titanate colloidal coating material.
[0006] The preparation method of the metal nanoparticle-modified strontium titanate colloidal coating material comprises the following steps:
[0007] Step 1: dispersing tetrabutyl titanate solution in anhydrous ethanol, then adding hydrochloric acid, acetylacetone and water, stirring evenly, and then aging to obtain colloid A; dissolving strontium chloride hexahydrate in anhydrous ethanol to obtain solution B, and adding solution B drop by drop into colloid A to obtain strontium titanium oxide colloid;
[0008] Step 2: coating a strontium titanium oxide colloidal coating on a substrate to obtain a sample;
[0009] Step 3: annealing the sample obtained in step 2 after heat preservation, and finally steam curing to obtain a strontium titanium oxide coating;
[0010] Step 4: Take a metal salt solution and apply it on the surface of the strontium titanium oxide coating by a heated spraying method, and then perform photoreduction deposition under light conditions to obtain a strontium titanium oxide coating modified with metal nanoparticles.
[0011] Preferably, in step 1, the volume ratio of tetrabutyl titanate and anhydrous ethanol is 5-10:50; in the strontium titanate colloid, the contents of hydrochloric acid, acetylacetone and deionized water account for 0.5-1%, 1.5-2% and 1-1.5% of the total content.
[0012] Preferably, in step 1, the volumes of anhydrous ethanol in solution B and colloid A are the same, and the molar content of strontium chloride hexahydrate is 8-12% of the molar amount of titanium ions in the strontium titanyl colloid.
[0013] Preferably, in step 4, the metal salt includes silver nitrate or copper sulfate; the solvent of the metal salt solution is water, and the concentration of the metal salt solution is 8 to 12 mg / mL.
[0014] Preferably, in step 2, the strontium titanium oxide colloidal coating is applied on the substrate by a dipping and pulling method, and the strontium titanium oxide colloidal coating is dried at room temperature after each application. After multiple dipping and pulling, a strontium titanium oxide colloidal coating with a certain thickness is obtained.
[0015] Preferably, in step three, the sample obtained in step two is placed in a blast drying oven for heat preservation, the drying temperature in the blast drying oven is 110-130°C; annealing is performed in a muffle furnace, the annealing temperature in the muffle furnace is 450-550°C; and steam curing is performed using water vapor, the steam curing time is 10-30 minutes.
[0016] Preferably, in step 4, a xenon lamp is used to simulate sunlight during the photodeposition process, and the irradiation time is 30 to 90 minutes.
[0017] The metal nanoparticle-modified strontium titanate colloidal coating material obtained by the above method is used in the antibacterial and anticorrosive coating of household products.
[0018] The beneficial effects of the present invention are:
[0019] 1) The present invention proposes a strontium titanium oxide colloidal coating modified with metal nanoparticles. By loading metal nanoparticles on strontium titanium oxide semiconductors, it can not only promote carrier migration and improve antibacterial properties, but also reduce the use of metal materials and reduce costs. It realizes the combination of two antibacterial materials, which can increase the antibacterial spectrum and increase the types of bacteria and molds that can be inhibited.
[0020] 2) The precursor of the present invention is prepared by a simple sol-gel method to obtain a uniform strontium titanium oxide colloidal coating, and the metal particles are modified on the coating surface by a spray-photodeposition method. By loading metal nanoparticles such as Ag and Cu on the strontium titanium oxide semiconductor to form a heterojunction, the separation and migration of photogenerated electron holes in the semiconductor can be effectively promoted, so that it produces more free radicals for efficient antibacterial. Compared with the prior art, the preparation steps of the present invention are simpler, the experimental conditions are relatively mild, and it has excellent antibacterial properties.
[0021] 3) The coating material proposed in the present invention can be evenly coated on the surface of household materials such as wooden boards, and can be used for antibacterial and anticorrosive purposes of household materials; due to the excellent photocatalytic properties and adhesion of the coating material, it can not only inhibit the growth of bacteria and mold and kill bacteria, but also has a certain moisture-proof effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 X-ray diffraction patterns of strontium titanate coating, silver particle modified strontium titanate coating, and copper particle modified strontium titanate coating;
[0023] Figure 2 The scanning electron microscope images of the silver particle modified strontium titanate coating and the copper particle modified strontium titanate coating (a is the SEM image of the silver particle modified strontium titanate colloidal coating, and the figure is the SEM image of the copper particle modified strontium titanate colloidal coating);
[0024] Figure 3 UV-visible diffuse reflectance spectra of strontium titanate coating, silver particle modified strontium titanate coating, and copper particle modified strontium titanate coating;
[0025] Figure 4 These are the antibacterial effect diagrams of blank control, silver particle modified strontium titanate coating, and copper particle modified strontium titanate coating. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with embodiments. The description of the following embodiments is only used to help understand the present invention. It should be noted that for ordinary persons in the art, without departing from the principle of the present invention, the present invention can also be modified in some ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0027] Embodiment 1
[0028] As an embodiment, this embodiment 1 proposes a method for preparing the metal nanoparticle-modified strontium titanium oxide colloidal coating material, which comprises coating the prepared strontium titanium oxide colloid on a substrate by means of immersion pulling, annealing, and steam curing, and then heating and spraying a silver nitrate or copper sulfate solution, reducing the silver or copper ions to silver or copper particles by photodeposition, and obtaining a metal nanoparticle-modified strontium titanium oxide colloidal coating material.
[0029] Specifically, the following steps are included:
[0030] Step 1: Preparation of strontium titanyl colloidal solution: Tetrabutyl titanate solution is dispersed in anhydrous ethanol, the volume ratio of tetrabutyl titanate to anhydrous ethanol is 6.8:50, and then hydrochloric acid, acetylacetone and water are added, stirred evenly, and then aged to obtain colloid A. The content of hydrochloric acid, acetylacetone and deionized water accounts for approximately 0.85%, 1.7% and 1.2% of the total content.
[0031] Strontium chloride hexahydrate is dissolved in anhydrous ethanol to obtain solution B. The amount of anhydrous ethanol added is consistent with that of the aged solution, and the molar content of strontium chloride hexahydrate added is 10% of the molar amount of titanium ions in the sol. Solution B is added dropwise to colloid A under stirring conditions to obtain strontium titanium oxide colloid.
[0032] Step 2: Applying strontium titanium oxide colloidal coating: Applying strontium titanium oxide colloidal coating on the cleaned substrate by dipping and pulling method, the substrate can be home furnishing materials such as solid wood board, particle board, composite board, etc. The dipping and pulling speed is 1 cm / min, and the pulling times are 3 to 5 times. Then dry at room temperature, and after multiple dipping and pulling, a strontium titanium oxide colloidal coating with a certain thickness is obtained to form a sample.
[0033] Step 3: Place the sample obtained in step 2 in a blast drying oven for a period of time, the drying temperature in the blast drying oven is 110-130°C, and the drying time is 1 hour; then place the sample in a muffle furnace for annealing, the annealing temperature in the muffle furnace is 450-550°C, and the annealing time is 1 hour. Finally, steam curing is performed, and the steam curing time is 10-30 minutes. A strontium titanium oxide coating is obtained.
[0034] Step 4: Photodeposition of metal nanoparticles: Take a certain amount of silver nitrate or copper sulfate aqueous solution and apply it on the surface of the strontium titanium oxide coating by heating spraying. The silver nitrate or copper sulfate solution used is a solution with a concentration of 10 mg / mL using water as the solvent, and the amount used is 300-900 μL. Then, photoreduction deposition is performed under light conditions to obtain a strontium titanium oxide coating modified with silver or copper nanoparticles. The light source used in the photodeposition process is a xenon lamp to simulate sunlight, and the irradiation time is 30-90 minutes.
[0035] Embodiment 2
[0036] As another embodiment, this embodiment 2 proposes, based on the embodiment 1, a preparation method of the metal nanoparticle-modified strontium titanyl colloidal coating material, and the specific process of preparing the silver particle-modified strontium titanyl colloidal coating material is as follows:
[0037] Step 1: Take 6.8 mL of tetrabutyl titanate and add it to 50 mL of anhydrous ethanol. Stir with a magnetic stirrer to evenly disperse the mixed solution. Then add 50 μL of hydrochloric acid to the mixed solution, add 1 mL of acetylacetone, and finally add 0.72 mL of water to stir it evenly. Aged for 24 hours to finally obtain a titanium oxide sol with a certain viscosity. Take 180 mg of strontium chloride hexahydrate and add it to 58.5 mL of anhydrous ethanol. Stir evenly until the strontium chloride hexahydrate is completely dissolved. Add the strontium chloride solution drop by drop into the titanium oxide sol under stirring to obtain a strontium titanium oxide colloid.
[0038] Step 2: Apply strontium titanium oxide colloidal coating on a 2.5 cm×2.5 cm optical glass sheet by dipping and pulling method, and the pulling times are 5 times.
[0039] Step 3: After natural drying, keep the mixture at 120° C. for 1 hour in a forced air drying oven, anneal it at 500° C. for 1 hour in a muffle furnace, and finally steam cure it in water vapor for 20 minutes to obtain a strontium titanium oxide colloidal coating material supported on optical glass.
[0040] Step 4: Place the above smear on a heating platform at 60°C, apply 500 μL of silver nitrate solution on the surface of the smear by spraying, and after the smear is dried, place the smear under simulated sunlight for 30 minutes to obtain a silver particle-modified strontium titanate colloidal coating material.
[0041] It should be noted that the parts in this embodiment that are the same or similar to those in the first embodiment can be referenced to each other and will not be described in detail in this application.
[0042] Embodiment 3
[0043] As another embodiment, this embodiment 3 is proposed on the basis of the embodiment 1. The specific process of preparing the copper particle modified strontium titanate colloidal coating material by this preparation method is as follows:
[0044] Step 1: Take 6.8 mL of tetrabutyl titanate and add it to 50 mL of anhydrous ethanol. Stir with a magnetic stirrer to evenly disperse the mixed solution. Then add 50 μL of hydrochloric acid to the mixed solution, add 1 mL of acetylacetone, and finally add 0.72 mL of water to stir it evenly. Aged for 24 hours to finally obtain a titanium oxide sol with a certain viscosity. Take 180 mg of strontium chloride hexahydrate and add it to 58.5 mL of anhydrous ethanol. Stir evenly until the strontium chloride hexahydrate is completely dissolved. Add the strontium chloride solution drop by drop into the titanium oxide sol under stirring to obtain a strontium titanium oxide colloid.
[0045] Step 2: Apply strontium titanium oxide colloidal coating on a 2.5 cm×2.5 cm optical glass sheet by dipping and pulling for 5 times.
[0046] Step 3: After natural drying, keep the mixture at 120° C. for 1 hour in a forced air drying oven, anneal it at 500° C. for 1 hour in a muffle furnace, and finally steam cure it in water vapor for 20 minutes to obtain a strontium titanium oxide colloidal coating material supported on optical glass.
[0047] Step 4: Place the above-mentioned smear on a heating platform at 60°C, apply 500 μL of copper sulfate solution on the surface of the smear by spraying, and after the smear is dried, place the smear under simulated sunlight for 30 minutes to obtain a copper particle-modified strontium titanium oxide colloidal coating material.
[0048] It should be noted that the parts in this embodiment that are the same or similar to those in Embodiments 1 and 2 can be referenced to each other and will not be described in detail in this application.
[0049] Comparative Example 1
[0050] As a comparative example, a method for preparing a strontium titanium oxide colloidal coating material comprises the following steps:
[0051] Step 1: Take 6.8 mL of tetrabutyl titanate and add it to 50 mL of anhydrous ethanol. Stir with a magnetic stirrer to evenly disperse the mixed solution. Then add 50 μL of hydrochloric acid to the mixed solution, add 1 mL of acetylacetone, and finally add 0.72 mL of water to stir it evenly. Aged for 24 hours to finally obtain a titanium oxide sol with a certain viscosity. Take 180 mg of strontium chloride hexahydrate and add it to 58.5 mL of anhydrous ethanol. Stir evenly until the strontium chloride hexahydrate is completely dissolved. Add the strontium chloride solution drop by drop into the titanium oxide sol under stirring to obtain a strontium titanium oxide colloid.
[0052] Step 2: Apply strontium titanium oxide colloidal coating on a 2.5 cm×2.5 cm optical glass sheet by dipping and pulling method, and the pulling times are 5 times.
[0053] Step 3: After natural drying, keep the mixture at 120° C. for 1 hour in a forced air drying oven, anneal it at 500° C. for 1 hour in a muffle furnace, and finally steam cure it in water vapor for 20 minutes to obtain a strontium titanium oxide colloidal coating material supported on optical glass.
[0054] Comparing Example 2, Example 3 and Comparative Example 1, the XRD spectra of the strontium titanate colloidal coating, the copper particle modified strontium titanate colloidal coating and the silver particle modified strontium titanate colloidal coating are as follows: Figure 1 As shown: the XRD patterns of the three coatings have the same trend. The intensity of the copper particle modified strontium titanate colloidal coating and the silver particle modified strontium titanate colloidal coating is lower than that of the strontium titanate colloidal coating. The samples do not show obvious diffraction peaks. The reason may be that the size of the prepared colloidal particles is small, which inhibits nucleation and limits crystal growth. In addition, the introduction of acetylacetone stabilizes the amorphous state, and it remains amorphous after annealing and steam curing.
[0055] SEM images of copper particle modified strontium titanate colloidal coating and silver particle modified strontium titanate colloidal coating are shown in Figure 2. Figure 2 As shown: Figure a is a SEM image of a silver particle modified strontium titanate colloidal coating. A dense film is covered on the substrate, which should be a strontium titanate colloidal coating, and many nanoparticles are distributed on the coating, which are silver nanoparticles. Figure b is a SEM image of a copper particle modified strontium titanate colloidal coating. Similarly, a dense film is covered on the substrate, but some thin-sheet structures appear on the surface, indicating that Cu grows into a thin-sheet structure during the reduction process.
[0056] UV-vis DRS of strontium titanate colloidal coating, copper particle modified strontium titanate colloidal coating and silver particle modified strontium titanate colloidal coating Figure 3 As shown: It can be seen that the metal nanoparticle-modified strontium titanium oxide colloidal coating material obtained by the method proposed in the present invention enhances the light absorption of the coating material by utilizing the loading of metal particles, among which the silver particle-modified strontium titanium oxide colloidal coating has the strongest light absorption, indicating that silver has a better enhancement effect on the light absorption performance of the strontium titanium oxide colloidal coating.
[0057] Embodiment 4
[0058] As another embodiment, this embodiment 4 proposes, based on embodiments 2 and 3, that the metal nanoparticle-modified strontium titanate colloidal coating material obtained by this method is used to inhibit Escherichia coli.
[0059] Dilute the E. coli liquid to an appropriate multiple, then drop the diluted liquid on the surface of the antibacterial coating, keep it in dark and light conditions for 5 minutes, then absorb the liquid droplets on the surface of the coating, evenly apply it on the prepared agar plate, and place it in a constant temperature box for 12 hours to ensure bacterial growth and antibacterial effect. After the culture is completed, observe the number of colonies on the agar plate to judge the antibacterial performance. Drop the liquid on a blank optical glass to test the antibacterial performance under dark and light conditions, and set up a blank control group.
[0060] The results of the antimicrobial test are as follows Figure 4 As shown, it can be seen from the results that under dark and light conditions, the culture medium of the blank control grows many and dense colonies, while under dark conditions, the culture medium of Example 2 and Example 3 has significantly fewer colonies, indicating that the coating material itself has good antibacterial properties. Under light conditions, the culture medium of Example 2 and Example 3 did not grow colonies, indicating that light can enhance the antibacterial properties of the coating material obtained by the method proposed in this application, reflecting the good photosensitivity and antibacterial properties of the coating material.
[0061] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
Claims
1. A method for preparing a metal nanoparticle-modified strontium titanate colloidal coating material, characterized in that: The following steps are involved: Step 1: dispersing tetrabutyl titanate solution in anhydrous ethanol, then adding hydrochloric acid, acetylacetone and water, stirring evenly, and then aging to obtain colloid A; dissolving strontium chloride hexahydrate in anhydrous ethanol to obtain solution B, and adding solution B drop by drop into colloid A to obtain strontium titanium oxide colloid; Step 2: coating a strontium titanium oxide colloidal coating on a substrate to obtain a sample; Step 3: annealing the sample obtained in step 2 after heat preservation, and finally steam curing to obtain a strontium titanium oxide coating; Step 4: Take a metal salt solution and apply it on the surface of the strontium titanium oxide coating by a heated spraying method, and then perform photoreduction deposition under light conditions to obtain a strontium titanium oxide coating modified with metal nanoparticles.
2. The method for preparing the metal nanoparticle-modified strontium titanyl colloidal coating material according to claim 1, characterized in that: In step 1, the volume ratio of tetrabutyl titanate and anhydrous ethanol is 5-10:50; in the strontium titanate colloid, the content of hydrochloric acid, acetylacetone and deionized water accounts for 0.5-1%, 1.5-2% and 1-1.5% of the total content.
3. The method for preparing the metal nanoparticle-modified strontium titanate colloidal coating material according to claim 1, characterized in that: In step 1, the volumes of anhydrous ethanol and colloid A in solution B are the same, and the molar content of strontium chloride hexahydrate is 8-12% of the molar amount of titanium ions in the strontium titanyl colloid.
4. The method for preparing the metal nanoparticle-modified strontium titanyl colloidal coating material according to claim 1, characterized in that: In step 4, the metal salt includes silver nitrate or copper sulfate; the solvent of the metal salt solution is water, and the concentration of the metal salt solution is 8 to 12 mg / mL.
5. The method for preparing the metal nanoparticle-modified strontium titanyl colloidal coating material according to claim 1, characterized in that: In step 2, a strontium titanium oxide colloidal coating is applied on the substrate by a dipping and pulling method. After each application of the strontium titanium oxide colloidal coating, the coating is dried at room temperature. After multiple dipping and pulling, a strontium titanium oxide colloidal coating with a certain thickness is obtained.
6. The method for preparing the metal nanoparticle-modified strontium titanyl colloidal coating material according to claim 1, characterized in that: In step three, the sample obtained in step two is placed in a blast drying oven for heat preservation, and the drying temperature in the blast drying oven is 110-130° C.; annealing is performed in a muffle furnace, and the annealing temperature in the muffle furnace is 450-550° C.; and steam curing is performed using water vapor, and the steam curing time is 10-30 minutes.
7. The method for preparing the metal nanoparticle-modified strontium titanyl colloidal coating material according to claim 1, characterized in that: In step 4, a xenon lamp is used to simulate sunlight during the photodeposition process, and the irradiation time is 30 to 90 minutes.
8. Use of the metal nanoparticle-modified strontium titanate colloidal coating material obtained by the method of claim 1 in antibacterial and anticorrosive coatings for household products.
Citation Information
Patent Citations
Antibacterial coating of copper-based loaded titanium dioxide hollow spheres as well as preparation and application of antibacterial coating
CN115820020A